The current value of terminology - Pozzi, María (Íkala, Revista de Lenguaje y Cultura, 2011)
When I asked myself about the current value of terminology, there were so many different aspects from which I could approach the subject that I decided, mainly for reasons of time, to touch on just one: the current value of terminology in specialized communication, since I believe that this is where its impact is most relevant.